Targeting the programmed cell death signaling mechanism with natural products for the treatment of acute pancreatitis: a review - Liu, Xuehuan; Dou, Baolei; Zhu, Qingjun; Liu, Chuanguo (Frontiers in Pharmacology, 2025)
Acute pancreatitis (AP) is a common critical disease in clinical practice, characterized by acute onset, rapid progression, aggressive conditions, and high lethality. Pancreatic acinar cell death is a central event in the pathological process of AP and a key factor in determining the extent of local or systemic inflammatory injury and overall prognosis. Programmed cell death (PCD) is a form of active cell death regulated by multiple genes, including apoptosis, autophagy, ferroptosis, pyroptosis, and necroptosis. PCD plays a critical role in eliminating unwanted organisms and damaged cells, which is of great significance. Numerous studies have demonstrated a strong association between various forms of PCD and AP, and targeted interventions in PCD signaling pathways and key targets can influence the progression of AP. Furthermore, existing research indicates that natural products sourced from plants, fruits, and vegetables exhibit considerable potential in targeting and regulating PCD for the treatment of AP. Therefore, this paper focuses on summarizing the common types of PCD in AP and discusses the specific signaling pathways and key targets reported in the treatment of AP using natural products. This review aims to provide a reference for natural products in guiding AP treatment and to lay the foundation for developing new drugs to effectively prevent and manage AP.